2008
DOI: 10.1677/joe-08-0226
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic protein 6 (BMP6) and BMP7 inhibit estrogen-induced proliferation of breast cancer cells by suppressing p38 mitogen-activated protein kinase activation

Abstract: Estrogen is involved in the development and progression of breast cancer. Here, we investigated the effects of bone morphogenetic proteins (BMPs) on breast cancer cell proliferation caused by estrogen using human breast cancer MCF-7 cells. MCF-7 cells express estrogen receptors (ESR1 and ESR2), BMP receptors, and SMAD signaling molecules. Estradiol and membrane-impermeable estradiol stimulated MCF-7 cell proliferation. Estradiol also reduced mRNA levels of ESR1, aromatase, and steroid sulfatase. Treatment with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 61 publications
6
60
0
Order By: Relevance
“…BMP6 neutralization in sera exerted little influence on cell growth (Fig. 9A), implying that BMP6 was not directly involved in regulating cancer cell growth, in agreement with the previous results [49,50]. DFO (at 100 μM) was used as a control to repress cell proliferation (Fig.…”
Section: Iron and Il-6 Jointly Promoted Tumor Cell Growthsupporting
confidence: 90%
“…BMP6 neutralization in sera exerted little influence on cell growth (Fig. 9A), implying that BMP6 was not directly involved in regulating cancer cell growth, in agreement with the previous results [49,50]. DFO (at 100 μM) was used as a control to repress cell proliferation (Fig.…”
Section: Iron and Il-6 Jointly Promoted Tumor Cell Growthsupporting
confidence: 90%
“…The results showed that inhibition of the expression of BMP6 significantly enhanced cell proliferation. Notably, BMP6 was found to inhibit cell proliferation in various cancer types including breast cancer, multiple myeloma, prostate cancer and skin tumors via multiple mechanisms including suppression of the p38-MAPK signaling pathway, cell cycle arrest and downregulation of AP-1 expression (17)(18)(19)(20). These data suggest that BMP6 may be a new diagnostic marker of breast cancer, and deregulation of BMP6 is involved in loss of proliferation control and failure to undergo cellular differentiation during tumorigenesis.…”
Section: Discussionmentioning
confidence: 95%
“…Aberrant BMP7 expression during tumour progression has been reported in a few cancer types, including colorectal cancer, breast cancer, melanoma, and prostate cancer (12,15,18,(21)(22)(23)(24)(25)(26). High levels of BMP7 have been detected in bone metastasis of prostate cancer, and breast carcinoma as they progress to a more aggressive phenotype (3,4,9,15). Upregulation of BMP7 expression in metastatic cells has been suggested to be a critical component of osteoblastic lesion development.…”
Section: Discussionmentioning
confidence: 99%
“…Of the factors related to metastasis, bone morphogenetic proteins (BMPs) have been recently shown to regulate the aggressiveness of cancer cells (1)(2)(3)(4)(5)(6)(7). BMPs are multifunctional signaling molecules belonging to the transforming growth factor-β (TGF-β) superfamily, which play important roles in multiple cellular processes such as cell growth, differentiation, migration and apoptosis in various types of cancer (8)(9)(10)(11)(12). The Smad-dependent signaling pathway has been proven to be the canonical pathway for BMP function (13).…”
Section: Introductionmentioning
confidence: 99%